Cirebon Law Protecting Creative Industries' Intellectual Property Rights - Mohamad Maarif; Yawaqit Anwar; Daniel Andi Martua Silitonga; Mohamad Sigit Gunawan; Solichin Solichin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
In Cirebon, there are a lot of Small and Medium Enterprises (SMEs) in the creative sector, however there is still generally not much management of intellectual property rights. The first issue raised by this study is the significance of intellectual property rights protection for small and medium-sized businesses in Cirebon's creative sector. Second, what part does the local government of Cirebon play in offering small and medium-sized businesses in the city the legal protection of their intellectual property rights? Using primary data, this study employs a juridical-empirical methodology. The study's findings indicate that, first, there is a tendency for the market for works produced in the creative industry to expand. This is because, in Cirebon, small and medium-sized enterprises (SMEs) account for 59% of GDP, and protecting intellectual property rights (IPR) for creative economy products is crucial to preserving the economic rights of original creators. Second, creating a website that offers IPR services is currently the role that local governments play in protecting SMEs' intellectual property rights.